Effect of Variation in Examination Delay Time on Hematocrit Results - Gusti Ayu Wulan Dian Kirana Dewi; Putu Ayu Parwati; Ni Luh Putu Thrisna Dewi (Jurnal Kesehatan Cendikia Jenius, 2026)
Hematocrit examination is an important parameter in assessing the balance of red blood cells; however, delays in examination frequently occur in laboratories and may affect result accuracy. Therefore, this study is necessary to determine the impact of delayed examination time on hematocrit results. The purpose of this study was to determine the effect of variations in examination delay time on hematocrit results. This study used an experimental design with a sample size of 10 respondents selected using purposive sampling. Data collection was conducted through immediate hematocrit examination and after a 2-hour delay in December 2025, then analyzed using the Shapiro-Wilk test and Paired Sample T-Test. The results showed that the mean hematocrit value for immediate examination was 42.0% and decreased to 41.8% after the delay, with a difference of 0.2%. Statistical analysis showed a p-value of 0.000 (p<0.05), indicating a significant effect of delay time on hematocrit results. However, the changes were relatively small and not clinically significant. In conclusion, examination delay affects blood sample stability; therefore, it should be considered in laboratory quality control, and further research using different methods is recommended.